COVID19 – An Approach Towards Using Traditional Medicine - Avishek Das; Pokhraj Guha; Avijit Dey (Journal of Pharmaceutical Research)
Viral infections in recent times creates life threatening conditions in patients. Recent covid infection is the major proof for this action in human immune system. As it has the capability to mutate in various different structures so, no counter mechanism is there to protect against the severe form. We have found many cases in Africa and other continents where mass destruction of human life occurs due to different viral infections. Many countries have their traditional practices to counteract the disease. From ancient times it has been found that traditional medicines plays a very important role in diagnosis of these infections. We have discussed various ethnopharmocologically important plant and their compounds which takes part in active role in anti inflammatory and antiviral effect on human populations. Different compounds isolated from different plant either it is root, stem or leaf can be very potential for diagnosing the diseases. It can also effect multiple organ system and try to cope up with various infections. The signal trunsduction pathway plays a very crucial role in activating different cell types and act according to their target cell. In recent times we develop various synthetic drugs to compensate the natural molecules but it has serious side effects in human and different viral strains areco adapted to those synthetic molecules in a very quick manner. So we have to go for the natural and try to use it in our daily life which slowly reduce the burden of the viral infection in our body. Keywords Covid, Synthetic Drugs, Ethnopharmacology, Anti Inflammatory